Hydrogel Containing an Oxygen Carrier With Hemoglobin From the Marine Worm Arenicola marina (M101) in the Management of Deep Burns - Ugo Lancien, MD, MSc; Pierre-Joachim Mahe, MD; Aline Lepelletier, MD; Elisabeth Leize-Zal, MD; Laurent Lantieri, MD, PhD; Pierre Perrot, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Summary:. A 34-year-old patient with no medical history was admitted following severe thermal burns (>85% of the body surface area), including deep second- and third-degree injuries. Surgical management aimed to heal the entire upper body (thorax, abdomen, and back) using topical oxygen therapy (TOT) on the deep second-degree burns, without burn excision or skin grafting, while processing conventional management of the remaining burned areas alongside specialized intensive care. TOT was performed using an innovative oxygenating dressing (HEMHealing, Hemarina SA, Morlaix, France) combined with conventional excisional, allograft, and autograft management (4 surgical steps) on the hands, upper limbs, and lower limbs; the protocol enabled graft-free healing of the abdomen, thorax, and back within around 5 weeks. Despite a prolonged healing time (47 d, beyond the dogma of 2–3 wk), at 12 months follow-up, the scars showed very little inflammation and no hypertrophy on the trunk and the back. The patient did not require compression garments on TOT-treated sites. We report the use of this innovative dressing—in parallel with resuscitation and conventional surgery—and the very favorable evolution of this patient confirms this choice in retrospect. We now need to consider other cases and studies to validate our initial clinical results.